Exploring Gender Differences on Attitude and Purchasing Intentions of Smartphone Brands: Array - Redda, Ephrem Habtemichael; Shezi, Nkosinamandla Erasmus (Acta Universitatis Danubius. Œconomica, 2021)
Understanding consumer behaviour is necessary for successful marketing of any product. Understanding gender differences on attitude and purchasing intention is vital in providing customised and targeted marketing. The purpose of this study was therefore to explore gender differences on attitude and purchasing intentions of smartphone brands among Generation Y students. This study used a quantitative research method. Data were collected using a self-administrated questionnaire and a cross-tabulation analysis was used. The Pearson Chi-squre, Cramer`s V and the Contingency coefficient values were computed to determine the significance and strength of the relationship. The results suggest that female Generation Y students have more favourable attitudes and behavioural intention toward smartphones compared to male. The implications of the findings of the study are that smartphone manufacturers need to design customised product and marketing materials based on gender differences and inclinations. Due to contradicting finding with existing literature, it is suggested that more studies need to be conducted before a conclusion is made on the subject.